Signifikansi Sertifikasi Halal Yang Mengalahkan Promosi Dalam Keputusan Pembelian Konsumen Muslim Di TikTok Shop - Rahel, Muhammad; Murtasiyah, Murtasiyah; Salsabilaturribi, Salsabilaturribi (PT. Student Rihlah Indonesia, 2025)
Amidst the rapid growth of e-commerce, particularly through platforms such as TikTok Shop, this study is crucial because it highlights the dilemma faced by Muslim consumers when making purchasing decisions, torn between the appeal of promotions and the urgency of halal certification. The main objective of this study is to analyze the simultaneous and partial effects of promotions and halal certification on purchasing decisions, as well as to identify the most dominant variables. Using a quantitative method with a questionnaire distributed to 371 respondents, the data was analyzed using multiple linear regression. The results of this study indicate that simultaneously, promotions and halal certification have a significant influence on purchasing decisions. However, a significant partial finding was discovered: only halal certification was proven to have a positive and significant influence (sig. 0.005). Conversely, promotion did not show a significant influence (sig. 0.258). The implication for businesses on TikTok Shop is clear: building the trust of Muslim consumers requires more than just promotion; it must be based on product halal assurance. This study provides insight that halal certification should be a priority strategy for building consumer loyalty, the impact of which is greater than the appeal of promotions alone.